Executive Presence Among Young Management and Law Students of SPMVV: An Interventional Study - Priyadarshini, Dr. G. Indira; Rajani, Dr. N. Sree; Reddy, Dr. V. Bhargavi (South Eastern European Journal of Public Health, 2025)
Executive presence (EP) is a critical attribute for success in leadership roles, combining confidence, communication skills, and the ability to inspire trust. This interventional study explores the impact of targeted EP training on management and law students at Sri Padmavati Mahila Visvavidyalayam (SPMVV). A total of 100 students participated. They underwent a structured EP enhancement program comprising workshop on nonverbal communication, public speaking, and self-awareness. Pre- and post-intervention assessments measured changes in key EP dimensions, including selfconfidence, body language, and verbal clarity. Results revealed a significant improvement in the group, highlighting the effectiveness of the intervention in equipping future leaders with essential executive competencies. This study underscores the importance of integrating EP development into higher education curricula, particularly for management and law disciplines.